Gamma irradiation on Alstroemeria aurea G. in vitro rhizomes: an approach to the appropriate dosage for breeding purposes - Aros, Danilo; Valdés, Santiago; Olate, Eduardo; Infante, Rodrigo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
Gamma irradiation has been widely used as a breeding technique to obtain new cultivars in ornamental species such as Alstroemeria, where several cultivars have been obtained through rhizome radiation. The optimum dosage for an appropriate induction of mutation must be considered for breeding purposes and it depends mainly on plant susceptibility. Thus in this study in vitro cultured rhizomes of Alstroemeria aurea were irradiated with a gamma source using different dosages to evaluate the direct effect produced. Damage and number of rhizome sprouting were observed and recorded during 61 days after irradiation. At the end of this period, rhizomes were weighted and mortality was evaluated. Both mortality and weight increased depending on dosage. All irradiated rhizomes showed early sprouting in comparison with control (0 Gy) and no significant difference in final number of shoots after 61 days among irradiated treatments was observed. Bleaching and necrosis was observed in all irradiated rhizomes and was more evident at higher doses. LD50 was established at about 40 Gy and the optimum dosage to induce mutation was suggested between 2.5 and 5 Gy, when the growth was reduced in 50%, and probably this dosage could be used for breeding purposes.